Screening and biological function of protein elicitor secreted from biocontrol agent Hhs.015. Issue 11 (4th October 2019) - Yan, Xia; Wu, Liqing; He, Dandan; Zhang, Yanan; Guo, Hongmei; Gao, Xiaoning; Wang, Nana; Huang, Lili
Abstract: Strain Hhs.015, a PGPR strain well‐studied for biocontrol of apple Valsa canker, was isolated from cucumber roots and classified as a new species of Saccharothrix yanglingensis. Hhs.015 was able to colonize apple tissue culture seedlings and trigger disease resistance. According to the whole‐genome sequence of S. yanglingensis Hhs.015, its secreted proteins were predicted and analysed, which can help to find out Hhs.015 functional substances that are involved in inducing plant system resistance and also the molecular mechanisms of the interaction between Hhs.015 and the host plants. Using the software SignalP4.1, TMHMM2.0, DAS‐TMfilter, HMMTOP, ScanProsite, PSORT and big‐PI predictor, 7, 379 ORFs of the genome of S. yanglingensis Hhs.015 were predicted and analysed. Moreover, the function of ORFs where the signal peptides come from was predicted by Swissprot database. The selected proteins were obtained by prokaryotic expression. Their effects in inducing plant resistance to the pathogen Valsa mali, resistance‐related enzyme activity and growth promotion analysis were evaluated. In total, 158 ORFs with known function, such as serine proteinase and transpeptidase, were identified; the remaining 142 ORFs were function‐unknown putative proteins. Five putative proteins were successfully obtained by prokaryotic expression, and the results showed that the protein named 5620g could enhance the plant disease resistance to the pathogen V. mali, inhibit the expansion of lesions and upregulate the defence‐related enzyme activity. The protein named 3176g could prolongate cucumber root. In conclusion, biocontrol strain Hhs.015 may secrete protein elicitors to improve plant resistance to the pathogenic microorganism and promote the growth of host plants.